Evidence of avian-mediated long distance dispersal in American tardigrades - Mogle, Matthew J.; Kimball, Scott A.; Miller, William R.; McKown, Richard D. (PeerJ, 2018)
Terrestrial tardigrades, commonly known as “water bears”, are part of a phylum of microscopic, aquatic invertebrates famous for cryptobiosis and space travel, but little is known about their modes of dispersal on Earth. Wind is assumed, but not truly demonstrated, to be the major method of global dispersal. Yet, some water bear distribution patterns cannot be explained by patterns of prevailing winds. Mammals and birds have been proposed as potential animal vectors. Importantly, most nearctic-neotropical migrant birds move north and south, with many crossing the equator, whereas prevailing winds move west to east or east to west but do not cross the equator. When multiplied by billions of birds over tens of millions of years, if the ectozoochory of tardigrades by birds is true then both regional and intercontinental patterns can be better explained. To test for the potential role of birds in tardigrade dispersal, the nests of 10 species for birds were examined. Seventy percent of nests were positive for tardigrades, demonstrating that some birds are in a position for transference. The carcasses of eight birds (six species) found dead from window strikes and a Sandhill Crane (Grus canadensis) found dead during routine surveys were also examined. Of the birds examined, 66% yielded tardigrades from two classes, three orders, and five species, including juveniles, adults, and eggs, suggesting that many bird species are potential vectors for many species of tardigrades. Our data support the hypothesis of avian-mediated long distance dispersal of tardigrades and provide evidence that further investigation is warranted.
Keywords: Bird nest; Migration; Transport; Ectozoochory; Dispersal; Plumage; Biogeography; Tardigrade